Dinamiks of «moter-placenta-foetus» system at physiological and patholigical conditions - Z. I. Mikashinowich; E. V. Olempieva; E. I. Shapovalova (Медицинский вестник Юга России, 2011)
Purpose: Estimation of free radicals oxidation and antioxidant status of «moter-placenta-foetus» functional sestem at physiological and complicated by cardiovascular pathology pregnancy.Materials and Methods: Erythrocytes and homogenates of placenta tissue taken from 75 pregnant was chosen as material for our investigation. There were estimated the activity of superoxide dismutase, catalase, glutathione peroxidase, glutathione reductase, the concentration of malondialdehyde, reduced glutathione.Results: It was estalished that pregnansy compicated by cardiiovacsular pathology was characterized by oxidative stress and disorder of different type of placental tissue metabolic activity/Summary: Estimation of these rates can be used in obstetrics and gynecology for the fetoplacental insufficiency severity degree.